Anti-aging preservative cable and preparation method thereof
Patent Information
- Application Number
- CN202611379128.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-07
- Publication Date
- 2026-10-27
AI Technical Summary
[0006]另一方面,现有抗老化外护套通常依赖单一橡胶或单一防老剂,难以同时应对热氧、紫外、臭氧和腐蚀介质
[0039]本发明采用第一FEP薄膜层和第二FEP薄膜层构成连续氟聚合物阻隔套,两层FEP薄膜沿相反螺旋方向绕包,搭接接缝沿电缆圆周方向错开,并分别对搭接部位进行表面热熔压合。该结构能够避免单层绕包或同向重合接缝形成连续螺旋渗透通道,延长酸液、碱液、盐雾及水汽向电缆内部迁移的路径,降低毛细渗透和温度循环泵吸作用引起的介质侵入,从而提高电缆在化工、电镀、沿海盐雾及湿热环境中的长期防腐蚀能力。
Smart Images

Figure SMS_2 
Figure SMS_3 
Figure SMS_4
Abstract
Description
Technical Field
[0001] This invention relates to the field of power cable technology, specifically to an anti-aging and anti-corrosion cable and its preparation method. Background Technology
[0002] Cables in chemical plants, electroplating production lines, coastal and salt spray areas, sewage treatment facilities, and outdoor energy equipment are subjected to the combined effects of acid mist, alkaline splashes, salt spray, damp heat, ultraviolet radiation, ozone, and repeated temperature changes over long periods. Corrosive media can cause plasticizer extraction, swelling, weight loss, hardening, and cracking in ordinary rubber or polyolefin sheaths; ultraviolet radiation and heat-oxygen interaction can also cause polymer chain breakage or excessive cross-linking, leading to a decrease in sheath elongation. Once cracks form in the sheath, corrosive media can penetrate the insulation layer along the cracks, wrapping seams, and interlayer gaps, further causing a decrease in insulation resistance, conductor surface corrosion, and premature cable failure.
[0003] Cross-linked polyethylene (XLPE) insulated power cables are widely used in conventional engineering projects. These cables rely on XLPE as the main insulation and polyvinyl chloride (PVC) or polyethylene (PE) as the outer sheath. They are inexpensive, easy to process, and suitable for conventional indoor and neutral outdoor power distribution scenarios. However, XLPE itself has limited resistance to acids, alkalis, and salt spray, and its molecular structure lacks media-stabilizing groups. At the same time, XLPE insulation lacks a fire-resistant mica buffer layer. When used for a long time in environments such as acid mist in chemical plants, high salt spray at the seaside, and acid and alkali splashes in electroplating, corrosive media can easily penetrate the PE / PVC sheath and then erode the XLPE insulation layer. On the one hand, acid and salt ions will destroy the polyethylene cross-linked network, causing the insulation volume resistivity to continuously decrease. On the other hand, under high temperature and ultraviolet coupling, XLPE is prone to thermal oxidative decomposition, and the sheath hardens and cracks prematurely. The medium travels along the cracks to the conductor, causing single-point leakage and short-circuit faults.
[0004] Currently, most XLPE insulated cables designed for corrosion conditions are optimized by using thickened sheaths and single-layer fluoroplastic wrapping. However, thickening the polyolefin sheath significantly reduces the cable's bending flexibility. Single-layer fluoroplastic film wrapping still has penetration channels at the overlap seams, and the interface bonding between the fluoroplastic layer and the XLPE insulation and outer rubber sheath is weak. Under temperature cycling and repeated bending, it is easy to delaminate and separate, which cannot meet the long-term (more than 20 years) stable operation requirements of chemical and coastal corrosion areas.
[0005] Existing corrosion-resistant cables commonly employ fluoroplastic extruded layers, fluoroplastic film wrapping layers, or corrosion-resistant rubber sheaths. While the fluoroplastic itself exhibits low dielectric permeability, a single-layer spiral-wound film can create short diffusion channels extending along the lap joint. Even with two layers wrapped in the same direction or overlapping seams, capillary action and thermal cycling can still create through-paths. When the fluoropolymer layer is bonded to the outer sheath using adhesives, the adhesives are prone to hydrolysis or embrittlement in high-temperature, humid, and acidic / alkaline environments. Improving mechanical bonding through perforations, riveting holes, or through-hole roughening directly damages the continuous barrier layer.
[0006] On the other hand, existing anti-aging outer sheaths typically rely on a single rubber or a single antioxidant, making it difficult to simultaneously cope with heat, oxygen, ultraviolet radiation, ozone, and corrosive media. Improving corrosion resistance often sacrifices low-temperature flexibility and ozone resistance, while improving flexibility may increase media absorption and thermal deformation. Some chlorine-containing rubbers release trace amounts of acidic products during long-term thermal aging, which, without acid capture and multi-stage stabilization measures, can accelerate the material's autocatalytic degradation. Summary of the Invention
[0007] In view of the above, the objective of this invention can be achieved through the following technical solutions:
[0008] In a first aspect, the present invention provides an anti-aging and anti-corrosion cable, which includes, in the radial direction from the inside out, a conductor, a fire-resistant mica wrapping layer, a heat-resistant silicone rubber insulation layer, a first FEP film layer, a second FEP film layer, a non-penetrating heat-setting FEP anchoring grid, and an anti-aging and anti-corrosion outer sheath.
[0009] Furthermore, the first FEP film layer is wrapped around the heat-resistant silicone rubber insulation layer along the first spiral direction, and the second FEP film layer is wrapped around the first FEP film layer along the second spiral direction opposite to the first spiral direction. The overlap seams of the first FEP film layer and the second FEP film layer are staggered along the circumference of the cable, and the overlap portions of the first FEP film layer and the second FEP film layer are surface heat-fused and pressed together, so that the first FEP film layer and the second FEP film layer together form a continuous fluoropolymer barrier sleeve without through holes.
[0010] Furthermore, the non-penetrating heat-set FEP anchoring grid includes a first FEP monofilament group wound in a left-handed direction and a second FEP monofilament group wound in a right-handed direction. The first and second FEP monofilament groups are partially fused with the surface of the second FEP film layer in the contact area, and do not penetrate the continuous fluoropolymer barrier sleeve. The anti-aging and anti-corrosion outer sheath covers the first and second FEP monofilament groups and fills the mesh gaps between adjacent FEP monofilaments to form a continuous colloidal bridge, thereby constituting a non-penetrating geometric anchoring of the anti-aging and anti-corrosion outer sheath.
[0011] Furthermore, the single-layer thickness of the first FEP film layer and the second FEP film layer are 0.05-0.15mm, the film width is 10-18mm, and the wrapping overlap rate is 45%-60%; the circumferential offset of the joint between the first FEP film layer and the second FEP film layer is 20%-50% of the cable circumference, and the total thickness of the continuous fluoropolymer barrier sleeve formed after hot-melt pressing is 0.12-0.30mm.
[0012] Furthermore, each of the first and second FEP monofilament groups includes 2-6 FEP monofilaments evenly arranged along the circumference of the cable; the diameter of the FEP monofilaments is 0.30-0.70mm, the pitch of the first and second FEP monofilament groups is 6-18mm, the absolute value of the winding angle of the two groups relative to the cable axis is equal to form a diamond grid, and the crossing angle of the two groups of FEP monofilaments is 40°-80°; interval-type dot-shaped or short strip-shaped welding zones are set along the length of the FEP monofilaments, the axial distance between adjacent welding zones is 3-12mm, and the axial length of a single welding zone is 1-5mm.
[0013] Furthermore, the depth to which the FEP monofilament is melted into the surface of the second FEP film layer is 15%-40% of the thickness of the second FEP film layer, and the minimum remaining thickness of the continuous fluoropolymer barrier sleeve at the fusion area is not less than 75% of the total thickness; the nominal thickness of the anti-aging and anti-corrosion outer sheath is 1.5-2.8mm, and the minimum coverage thickness of the anti-aging and anti-corrosion outer sheath on the outer side of the top of the FEP monofilament is not less than 0.8mm.
[0014] Further, the anti-aging and anti-corrosion outer sheath comprises, by weight parts: 50-60 parts chlorinated polyethylene rubber, 20-30 parts hydrogenated nitrile rubber, 15-25 parts ethylene propylene diene monomer (EPDM) rubber, 18-26 parts carbon black N550, 12-20 parts calcined kaolin, 8-14 parts precipitated barium sulfate, 3-5 parts active magnesium oxide, 1.0-1.8 parts antioxidant 445, 0.4-0.8 parts antioxidant RD, 0.3-0.7 parts ultraviolet absorber UV-531, 0.3-0.8 parts hindered amine light stabilizer 944, 1.0-2.0 parts microcrystalline wax, 5-9 parts trioctyl trimellitate, 0.5-1.0 parts stearic acid, 1.0-1.6 parts dicumyl peroxide, and 0.5-1.0 parts triallyl isocyanurate.
[0015] Furthermore, the heat-resistant silicone rubber insulating layer comprises, by weight, 100 parts of methyl vinyl phenyl silicone rubber, 24-32 parts of precipitated silica, 10-18 parts of spherical alumina, 8-15 parts of calcined kaolin, 1.0-2.0 parts of iron oxide red, 2-5 parts of phenyl silicone oil, and 0.8-1.2 parts of 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane.
[0016] Furthermore, the conductor is formed by layering nickel-plated soft copper monofilaments in a 1+6+12+18 structure, with the diameter of the nickel-plated soft copper monofilaments being 0.18-0.30 mm, the nickel layer thickness being 1-4 μm, and the conductor compaction coefficient being 0.87-0.91; the pitch ratios of the innermost strand, the middle strand, and the outermost strand are 9-11, 8-10, and 7-9, respectively; the fire-resistant mica wrapping layer uses phlogopite tape with a thickness of 0.06-0.14 mm, and the wrapping overlap rate is 20%-45%; the nominal thickness of the heat-resistant silicone rubber insulation layer is 1.0-1.8 mm.
[0017] Secondly, the present invention provides a method for preparing the above-mentioned anti-aging and anti-corrosion cable, comprising the following steps:
[0018] S1: Nickel-plated soft copper monofilaments are stranded in layers to form a conductor, gilt mica tape is wrapped around the conductor, and heat-resistant silicone rubber insulation is extruded. After hot air vulcanization and cooling for shaping, the insulated wire core is obtained.
[0019] S2: Wrap a first FEP film layer around the insulated wire core along a first spiral direction, and briefly heat and press the overlapping portion of the first FEP film layer together and then cool it; then wrap a second FEP film layer along a second spiral direction opposite to the first spiral direction, so that the overlapping seam of the first and second FEP film layers is staggered in the circumferential direction, and briefly heat and press the overlapping portion of the second FEP film layer together to form a continuous fluoropolymer barrier sleeve:
[0020] S3: FEP resin is extruded, drawn, sizing, and annealed to form FEP monofilaments. Two sets of FEP monofilaments are wound around the second FEP film layer in left-hand and right-hand directions, respectively, and the FEP monofilaments are partially fused to the surface of the second FEP film layer to form a non-penetrating heat-set FEP anchoring grid.
[0021] S4: Prepare anti-aging and anti-corrosion outer sheath material, and extrude the anti-aging and anti-corrosion outer sheath material onto the outside of the non-penetrating heat-set FEP anchoring grid, and form an anti-aging and anti-corrosion outer sheath by continuous hot air vulcanization.
[0022] S5: After vulcanization, the cable undergoes post-heat treatment and graded cooling to obtain an anti-aging and corrosion-resistant cable.
[0023] Furthermore, in S1, the stranding speed of the nickel-plated soft copper monofilament is 15-35 m / min, and the tension of each stranded monofilament is 2-6 N; the wrapping speed of the phlogopite tape is 10-30 m / min, and the wrapping tension is 3-8 N.
[0024] Furthermore, the heat-resistant silicone rubber insulation material in S1 is extruded using a rubber extruder. The temperature of the feeding section of the rubber extruder is 45-55℃, the temperature of the plasticizing section is 55-65℃, the temperature of the homogenizing section is 60-75℃, the temperature of the die head is 70-85℃, and the screw speed is 20-35 rpm. The hot air vulcanization temperature is 180-205℃, the vulcanization time is 6-10 minutes, and after vulcanization, it is cooled with room temperature air until the surface temperature of the insulated wire core does not exceed 50℃.
[0025] Furthermore, in S2, the wrapping linear speeds of the first FEP film layer and the second FEP film layer are 4-12 m / min, and the wrapping tensions are 3-8 N, respectively.
[0026] Furthermore, after the first FEP film layer in S2 is wrapped, a ring-shaped hot air heater is used to heat and press the overlapping area of the film layer. After cooling, the second FEP film layer is wrapped, and the overlapping area of the second FEP film layer is heated and pressed in the same way. During the two hot melt pressing processes, the outer surface temperature of the corresponding FEP film layer is 300-330℃, and the pressing pressure is 0.08-0.24MPa. During the two hot melt pressing processes, the highest temperature of the outer surface of the heat-resistant silicone rubber insulation layer does not exceed 180℃. After each hot melt pressing, room temperature air is used for cooling to reduce the surface temperature of the corresponding FEP film layer to below 80℃.
[0027] Further, in step S3, the FEP resin is dried at 110-130℃ for 3-5 hours and then melt-extruded using a single-screw extruder. The temperature of the feeding section of the single-screw extruder is 300-320℃, the temperature of the compression section is 320-340℃, the temperature of the metering section is 335-360℃, the temperature of the die head is 330-355℃, and the screw speed is 20-45 rpm. A circular die with an aperture of 0.35-1.15 mm is selected according to the target monofilament diameter, and the melt extrusion rate is adjusted accordingly. After the melt is cooled by air and drawn and sized at a traction ratio of 1.2-2.5, it is continuously annealed and shaped at 220-245℃ for 30-90 seconds, and then cooled to below 60℃ to obtain FEP monofilaments with a diameter deviation of no more than ±0.03 mm.
[0028] Furthermore, in S3, the first and second FEP monofilament groups use the same pitch, and the absolute values of the winding angles of the two groups relative to the cable axis are equal to form a diamond grid; the winding linear speed of the two groups is 3-12 m / min, and the monofilament tension is 2-6 N; the FEP monofilaments and the second FEP film layer are intermittently welded using a grooved limiting pressure roller, with a local welding temperature of 260-280℃, a single-point heating time of 0.5-2.5 s, and a pressure roller pressure of 0.03-0.15 MPa, and the welding depth of the FEP monofilaments is controlled by the grooved limiting pressure roller; after welding, an online inspection is performed using a 3-8 kV high-voltage spark to confirm that the continuous fluoropolymer barrier sleeve has no through-hole defects.
[0029] Furthermore, the preparation method of the heat-resistant silicone rubber insulating material is as follows:
[0030] A1: Add methyl vinyl phenyl silicone rubber and phenyl silicone oil to a mixer and mix at 50-65℃ and 30-50rpm for 3-5 minutes; add precipitated silica in two batches, mixing for 3-5 minutes after each addition; then add spherical alumina, calcined kaolin and iron oxide red, and continue mixing at 55-75℃ and 40-60rpm for 8-12 minutes, controlling the discharge temperature at 90-100℃ to obtain the insulating base adhesive;
[0031] A2: Cool the insulating base rubber to below 50℃, add 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane, and pass it through a two-roll mill with a roll temperature of 30-45℃, a front-to-back roll speed ratio of 1:1.1-1:1.3, and a roll gap of 0.5-1.0mm 3-5 times; let the passed rubber compound stand at 20-30℃ for 4-12 hours to obtain heat-resistant silicone rubber insulating material;
[0032] Furthermore, the preparation method of the anti-aging and anti-corrosion outer sheath material is as follows:
[0033] B1: Add chlorinated polyethylene rubber and EPDM rubber to a mixer and mix at 70-85℃ and 30-45rpm for 2-4 minutes. Then add hydrogenated nitrile butadiene rubber and continue mixing for 2-4 minutes. Add activated magnesium oxide and stearic acid and mix for 2-3 minutes. Add carbon black N550, calcined kaolin, precipitated barium sulfate, and trioctyl trimellitate. After all the additions are complete, continue mixing at 75-95℃ and 40-55rpm for 8-12 minutes.
[0034] B2: Add antioxidant 445, antioxidant RD, UV absorber UV-531, hindered amine light stabilizer 944 and microcrystalline wax, continue mixing at 70-85℃ for 3-5 minutes and then discharge the glue, controlling the discharge temperature to 95-105℃.
[0035] B3: Cool the rubber compound to below 50℃, add dicumyl peroxide and triallyl isocyanurate on an open mill with a roller temperature of 30-45℃, a front-to-back roller speed ratio of 1:1.1-1:1.3, and a roller gap of 0.6-1.2mm, and pass it through the mill 3-5 times; let the rubber compound that has passed through the mill stand at 20-30℃ for 6-12 hours to obtain an anti-aging and anti-corrosion outer sheath material.
[0036] Furthermore, the anti-aging and anti-corrosion outer sheath material in S4 is extruded using a rubber extruder. The temperature of the feeding section of the rubber extruder is 45-55℃, the temperature of the plasticizing section is 55-65℃, the temperature of the homogenizing section is 60-70℃, the temperature of the die head is 65-80℃, and the screw speed is 15-30 rpm. The nominal thickness of the anti-aging and anti-corrosion outer sheath formed after extrusion is 1.5-2.8 mm. For the dicumyl peroxide / trimethylene isocyanurate crosslinking system, the continuous hot air vulcanization temperature is 165-175℃ and the vulcanization time is 8-12 min.
[0037] Furthermore, the post-heat treatment temperature in S5 is 140-155℃ and the post-heat treatment time is 1-3h.
[0038] The beneficial effects of this invention are:
[0039] This invention employs a first FEP film layer and a second FEP film layer to form a continuous fluoropolymer barrier sleeve. The two FEP film layers are wrapped in opposite spiral directions, and the overlapping seams are staggered along the circumference of the cable. The overlapping areas are then surface-heat-sealed. This structure avoids the formation of continuous spiral penetration channels by single-layer wrapping or overlapping seams in the same direction, extending the path for acids, alkalis, salt spray, and water vapor to migrate into the cable. It also reduces media intrusion caused by capillary penetration and temperature-cycle pumping, thereby improving the cable's long-term corrosion resistance in chemical, electroplating, coastal salt spray, and humid environments.
[0040] This invention involves setting a non-penetrating heat-set FEP anchoring grid outside the second FEP film layer, composed of a left-handed first FEP monofilament group and a right-handed second FEP monofilament group. The FEP monofilaments are only partially fused to the surface of the second FEP film layer and do not penetrate the continuous fluoropolymer barrier sleeve. The outer sheath covers the cross-arranged FEP monofilaments, forming continuous colloidal bridges between adjacent monofilaments. This allows for the formation of distributed geometric anchoring without drilling, using easily aging adhesives, or compromising the barrier integrity, improving the axial holding force and stress transfer uniformity between layers, and suppressing sheath movement, torsion, and delamination during temperature cycling, winding, and repeated bending processes.
[0041] The anti-aging and corrosion-resistant outer sheath of this invention adopts a co-crosslinking system of chlorinated polyethylene rubber, hydrogenated nitrile rubber, and EPDM rubber. It achieves acid product capture, thermo-oxidative free radical inhibition, UV absorption, and surface migration protection through active magnesium oxide, antioxidant 445, antioxidant RD, UV absorber UV-531, hindered amine light stabilizer 944, and microcrystalline wax, respectively. The heat-resistant silicone rubber insulation layer, through the synergistic effect of precipitated silica reinforcement, spherical alumina thermal conductivity, calcined kaolin filling, and iron oxide red heat-resistant stabilization, reduces local heat accumulation and maintains high-temperature electrical performance, enabling the cable to possess resistance to thermo-oxidative aging, UV aging, ozone resistance, acid and alkali corrosion resistance, salt spray resistance, and long-term electrical stability. Detailed Implementation
[0042] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0043] The main sources of materials used in the embodiments of this application are as follows:
[0044] The phlogopite tape is branded SCOTER and was purchased from Dongguan SCOTER New Materials Co., Ltd.
[0045] The FEP film, grade DS610, model XH6030PRVZU4, was purchased from Suzhou Xinshengwang Plastics Co., Ltd.
[0046] The FEP resin, grade DS618C, was purchased from Dongguan Suming Plastic Raw Materials Co., Ltd.
[0047] The methyl vinyl phenyl silicone rubber has a phenyl content of 15% and a vinyl content of 0.23%, and was purchased from Ningbo Daoruo Organosilicon Co., Ltd.
[0048] The active magnesium oxide has a magnesium oxide content of ≥90.0%, a calcium oxide content of ≤2%, and a chloride content of ≤0.05%, and was purchased from Jiangsu Zehui Magnesium-based New Materials Technology Co., Ltd.
[0049] The precipitated silica had a particle size of 2000 mesh and was purchased from Shandong Kason New Materials Co., Ltd.
[0050] The spherical alumina, model PAT-50, was purchased from Qinghe County Chaotai Metal Materials Co., Ltd.
[0051] The calcined kaolin has a mesh size of 1250 and was purchased from Lingshou County Baofeng Mica Processing Co., Ltd.
[0052] The precipitated barium sulfate had a mesh size of 1250 and was purchased from Shijiazhuang Zhouting Mineral Products Co., Ltd.
[0053] Example 1
[0054] A method for preparing an anti-aging and corrosion-resistant cable includes the following steps:
[0055] S1: Select nickel-plated soft copper monofilaments with a diameter of 0.18mm and a nickel layer thickness of 1μm, and strand them in layers according to a 1+6+12+18 structure. The pitch ratios of the innermost, middle, and outermost strands are 9, 8, and 7, respectively, and the conductor compaction coefficient is 0.87. The stranding speed is 15m / min, and the tension of each stranded monofilament is 2N. A 0.06mm thick phlogopite tape is wrapped around the conductor at a linear speed of 10m / min, with an overlap of 20% and a wrapping tension of 3N. Heat-resistant silicone rubber insulation material is extruded onto the phlogopite tape using a rubber extruder. The temperatures of the feeding section, plasticizing section, homogenizing section, and die head of the rubber extruder are 45℃, 55℃, 60℃, and 70℃, respectively, the screw speed is 20rpm, and the nominal thickness of the insulation layer is 1.0mm. The insulation is continuously vulcanized with hot air at 180℃ for 6 minutes, and then cooled with room temperature air until the surface temperature of the insulated wire core does not exceed 50℃, thus obtaining the insulated wire core.
[0056] S2: Using an FEP film with a thickness of 0.06mm and a width of 10mm, the first FEP film layer is wrapped in the first spiral direction with an overlap rate of 45%, a wrapping linear speed of 4m / min, and a wrapping tension of 3N. A ring-shaped hot air heater is used to raise the outer surface temperature of the first FEP film layer to 300℃, and the overlap is pressed together with a pressure of 0.08MPa. During this hot melt pressing process, the maximum temperature of the outer surface of the heat-resistant silicone rubber insulation layer is controlled not to exceed 180℃, and it is cooled to a surface temperature below 80℃. Then, an FEP film of the same specification is used... An EP film is wrapped around a second FEP film layer in a second spiral direction opposite to the first spiral direction, so that the overlap seam of the second FEP film layer is offset from the overlap seam of the first FEP film layer by 20% of the cable circumference in the circumferential direction; the outer surface temperature of the second FEP film layer reaches 300°C, and the overlap part is heat-melted and pressed together with a pressure of 0.08MPa. During this heat-melting and pressing process, the maximum temperature of the outer surface of the heat-resistant silicone rubber insulation layer is controlled not to exceed 180°C. After cooling, a continuous fluoropolymer barrier sleeve with a total thickness of 0.12mm is formed.
[0057] S3: The FEP monofilaments are divided into a first FEP monofilament group and a second FEP monofilament group, each group consisting of two FEP monofilaments evenly arranged along the circumference of the cable; the two groups of FEP monofilaments are wound around the second FEP film layer in left-hand and right-hand directions respectively, with a pitch of 6mm. The absolute values of the winding angles of the two groups relative to the cable axis are equal, forming a diamond grid. The crossing angle of the two groups of FEP monofilaments is 40°, the winding linear speed is 3m / min, and the monofilament tension is 2N; short, spaced-apart welding zones are set along the length of the FEP monofilaments, with the axis of adjacent welding zones... The spacing is 3mm, and the axial length of a single weld zone is 1mm. A grooved limiting pressure roller is used to perform local welding under the conditions of 260℃, single-point heating time of 0.5s, and pressure roller pressure of 0.03MPa, so that the depth of the FEP monofilament fused into the surface of the second FEP film layer is 15% of the thickness of the second FEP film layer. The minimum remaining thickness of the continuous fluoropolymer barrier sleeve at the weld zone is not less than 90% of the total thickness. After welding, a 3kV high-voltage spark online inspection is used to confirm that there are no penetration defects in the continuous fluoropolymer barrier sleeve, and a non-penetrating heat-set FEP anchor grid is obtained.
[0058] S4: The anti-aging and anti-corrosion outer sheath material is extruded onto the outside of the non-penetrating heat-set FEP anchoring grid using a rubber extruder. The temperatures of the feeding section, plasticizing section, homogenizing section, and die head of the rubber extruder are 45℃, 55℃, 60℃, and 65℃, respectively, and the screw speed is 15 rpm. This forms an anti-aging and anti-corrosion outer sheath with a nominal thickness of 1.5 mm. The minimum coverage thickness of the outer sheath on the outside of the top of the FEP monofilament is 0.8 mm. The material is then continuously vulcanized with hot air at 165℃ for 8 minutes.
[0059] S5: After vulcanization, the cable is heat-treated at 140℃ for 1 hour, then slowly cooled in a circulating hot air environment at 80℃ for 20 minutes, and then cooled in room temperature air until the surface temperature of the cable does not exceed 40℃, thus obtaining an anti-aging and anti-corrosion cable.
[0060] Preparation of heat-resistant silicone rubber insulation material: By weight, take 100 parts of methyl vinyl phenyl silicone rubber, 24 parts of precipitated silica, 10 parts of spherical alumina, 8 parts of calcined kaolin, 1.0 part of iron oxide red, 2 parts of phenyl silicone oil and 0.8 parts of 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane.
[0061] A1: Add methyl vinyl phenyl silicone rubber and phenyl silicone oil to a mixer and mix at 50°C and 30 rpm for 3 min; add precipitated silica in two batches, mixing for 3 min after each addition; then add spherical alumina, calcined kaolin and iron oxide red, and continue mixing at 55°C and 40 rpm for 8 min, controlling the discharge temperature at 90°C to obtain the insulating base adhesive;
[0062] A2: Cool the insulating base rubber to below 50°C, add 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane, and pass it through a two-roll mill with a roll temperature of 30°C, a front-to-back roll speed ratio of 1:1.1, and a roll gap of 0.5mm three times; let the rubber compound after passing through the two-roll mill stand at 20°C for 4 hours to obtain heat-resistant silicone rubber insulating material.
[0063] Preparation of FEP monofilament: FEP resin was dried at 110℃ for 3 hours and then fed into a single-screw extruder. The temperatures of the feeding section, compression section, metering section and die head were 300℃, 320℃, 335℃ and 330℃ respectively, and the screw speed was 20 rpm. A circular die with a diameter of 0.35 mm was used, and the extrusion rate was adjusted to stabilize the melt. After air cooling, the melt was drawn and sized at a traction ratio of 1.2. Then, it was continuously annealed and shaped at 220℃ for 30 seconds and cooled to below 60℃ to obtain FEP monofilament with a diameter of 0.3 mm and a diameter deviation of no more than ±0.03 mm.
[0064] Preparation of anti-aging and anti-corrosion outer sheath material: By weight, take 50 parts of chlorinated polyethylene rubber, 20 parts of hydrogenated nitrile rubber, 15 parts of ethylene propylene diene monomer (EPDM) rubber, 18 parts of carbon black N550, 12 parts of calcined kaolin, 8 parts of precipitated barium sulfate, 3 parts of active magnesium oxide, 1.0 part of antioxidant 445, 0.4 parts of antioxidant RD, 0.3 parts of ultraviolet absorber UV-531, 0.3 parts of hindered amine light stabilizer 944, 1.0 part of microcrystalline wax, 5 parts of trioctyl trimellitate, 0.5 parts of stearic acid, 1.0 part of dicumyl peroxide, and 0.5 parts of triallyl isocyanurate.
[0065] B1: Add chlorinated polyethylene rubber and EPDM rubber to a mixer and mix at 70°C and 30 rpm for 2 minutes. Then add hydrogenated nitrile butadiene rubber and continue mixing for 2 minutes. Add activated magnesium oxide and stearic acid and mix for 2 minutes. Add carbon black N550, calcined kaolin, precipitated barium sulfate, and trioctyl trimellitate. After all the ingredients are added, continue mixing at 75°C and 40 rpm for 8 minutes.
[0066] B2: Add antioxidant 445, antioxidant RD, UV absorber UV-531, hindered amine light stabilizer 944 and microcrystalline wax, continue mixing at 70℃ for 3 minutes and then discharge the glue, controlling the discharge temperature to 95℃.
[0067] B3: Cool the rubber compound to below 50°C, add dicumyl peroxide and triallyl isocyanurate to a two-roll mill with a roll temperature of 30°C, a front-to-back roll speed ratio of 1:1.1, and a roll gap of 0.6mm, and pass it through the mill three times; let the rubber compound that has passed through the mill stand at 20°C for 6 hours to obtain an anti-aging and anti-corrosion outer sheath material.
[0068] Example 2
[0069] A method for preparing an anti-aging and corrosion-resistant cable includes the following steps:
[0070] S1: Select nickel-plated soft copper monofilaments with a diameter of 0.24 mm and a nickel layer thickness of 2.5 μm, and strand them in layers according to a 1+6+12+18 structure. The pitch ratios of the innermost, middle, and outermost strands are 10, 9, and 8, respectively, and the conductor compaction coefficient is 0.89. The stranding speed is 25 m / min, and the tension of each strand of monofilament is 4 N. Wrap a 0.1 mm thick phlogopite tape around the conductor at a line speed of 20 m / min, with a wrapping overlap rate of 32.5%. The wrapping tension is 5.5N; the heat-resistant silicone rubber insulation material is extruded onto the outside of the phlogopite mica tape through a rubber extruder. The temperatures of the feeding section, plasticizing section, homogenizing section, and die head of the rubber extruder are 50℃, 60℃, 67.5℃, and 77.5℃ respectively, the screw speed is 27.5rpm, and the nominal thickness of the insulation layer is 1.4mm; continuous hot air vulcanization is carried out at 192.5℃ for 8 minutes, followed by cooling with room temperature air until the surface temperature of the insulated wire core does not exceed 50℃, thus obtaining the insulated wire core;
[0071] S2: Using an FEP film with a thickness of 0.1mm and a width of 14mm, the first FEP film layer is wrapped in the first spiral direction, with a wrapping overlap rate of 52.5%, a wrapping linear speed of 8m / min, and a wrapping tension of 5.5N; a ring-shaped hot air heater is used to raise the outer surface temperature of the first FEP film layer to 315℃, and the overlap is pressed together with a pressure of 0.16MPa. During this hot melt pressing process, the maximum temperature of the outer surface of the heat-resistant silicone rubber insulation layer is controlled not to exceed 180℃, and it is cooled to a surface temperature below 80℃; then, the same specifications are used... The FEP film is wrapped around the second FEP film layer in a second spiral direction opposite to the first spiral direction, so that the overlap seam of the second FEP film layer is offset from the overlap seam of the first FEP film layer by 35% of the cable circumference in the circumferential direction; the outer surface temperature of the second FEP film layer reaches 315°C, and the overlap part is heat-melted and pressed together with a pressure of 0.16MPa. During this heat-melting and pressing process, the maximum temperature of the outer surface of the heat-resistant silicone rubber insulation layer is controlled not to exceed 180°C. After cooling, a continuous fluoropolymer barrier sleeve with a total thickness of 0.2mm is formed.
[0072] S3: The FEP monofilaments are divided into a first FEP monofilament group and a second FEP monofilament group, each group consisting of 4 FEP monofilaments evenly arranged along the circumference of the cable; the two groups of FEP monofilaments are wound around the second FEP film layer in left-hand and right-hand directions respectively, with a pitch of 12mm. The absolute values of the winding angles of the two groups relative to the cable axis are equal and form a diamond grid. The crossing angle of the two groups of FEP monofilaments is 60°, the winding linear speed is 7.5m / min, and the monofilament tension is 4N; short strip-shaped fusion splicing zones are set along the length of the FEP monofilaments, with axial spacing between adjacent fusion splicing zones. The distance between welds is 7.5 mm, and the axial length of a single weld zone is 3 mm. A grooved limiting pressure roller is used to perform local welding under the conditions of 270℃, single-point heating time of 1.5 s and pressure roller pressure of 0.09 MPa, so that the depth of the FEP monofilament fused into the surface of the second FEP film layer is 27.5% of the thickness of the second FEP film layer. The minimum remaining thickness of the continuous fluoropolymer barrier sleeve at the weld zone is not less than 85% of the total thickness. After welding, a 5.5 kV high-voltage spark online inspection is used to confirm that the continuous fluoropolymer barrier sleeve has no penetration defects, and a non-penetrating heat-set FEP anchor grid is obtained.
[0073] S4: The anti-aging and corrosion-resistant outer sheath material is extruded onto the outside of the non-penetrating heat-set FEP anchoring grid using a rubber extruder. The temperatures of the feeding section, plasticizing section, homogenizing section, and die head of the rubber extruder are 50℃, 60℃, 65℃, and 72.5℃, respectively, and the screw speed is 22.5 rpm. This forms an anti-aging and corrosion-resistant outer sheath with a nominal thickness of 2.15 mm. The minimum coverage thickness of the outer sheath on the outside of the top of the FEP monofilament is 1.0 mm. The material is then continuously vulcanized with hot air at 170℃ for 10 minutes.
[0074] S5: After vulcanization, the cable is heat-treated at 147.5℃ for 2 hours, then slowly cooled in a 90℃ circulating hot air environment for 30 minutes, and then cooled in room temperature air until the surface temperature of the cable does not exceed 40℃, thus obtaining an anti-aging and anti-corrosion cable.
[0075] Preparation of heat-resistant silicone rubber insulation material: By weight, take 100 parts of methyl vinyl phenyl silicone rubber, 28 parts of precipitated silica, 14 parts of spherical alumina, 11.5 parts of calcined kaolin, 1.5 parts of iron oxide red, 3.5 parts of phenyl silicone oil and 1.0 part of 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane;
[0076] A1: Add methyl vinyl phenyl silicone rubber and phenyl silicone oil to a mixer and mix at 57.5℃ and 40 rpm for 4 min; add precipitated silica in two batches, mixing for 4 min after each addition; then add spherical alumina, calcined kaolin and iron oxide red, and continue mixing at 65℃ and 50 rpm for 10 min, controlling the discharge temperature at 95℃ to obtain insulating base rubber;
[0077] A2: Cool the insulating base rubber to below 50℃, add 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane, and pass it through a two-roll mill with a roll temperature of 37.5℃, a front-to-back roll speed ratio of 1:1.2, and a roll gap of 0.75mm 4 times; let the rubber compound after passing through the two-roll mill stand at 25℃ for 8 hours to obtain heat-resistant silicone rubber insulating material;
[0078] Preparation of FEP monofilament: FEP resin was dried at 120℃ for 4 hours and then fed into a single-screw extruder. The temperatures of the feeding section, compression section, metering section, and die head were 310℃, 330℃, 347.5℃, and 342.5℃, respectively, and the screw speed was 32.5 rpm. A circular die with a diameter of 0.72 mm was used, and the extrusion rate was adjusted to stabilize the melt. After air cooling, the melt was drawn and sized at a traction ratio of 1.85. Then, it was continuously annealed and shaped at 232.5℃ for 60 seconds and cooled to below 60℃ to obtain FEP monofilament with a diameter of 0.5 mm and a diameter deviation of no more than ±0.03 mm.
[0079] Preparation of anti-aging and anti-corrosion outer sheath material: By weight, take 55 parts of chlorinated polyethylene rubber, 25 parts of hydrogenated nitrile rubber, 20 parts of ethylene propylene diene monomer (EPDM) rubber, 22 parts of carbon black N550, 16 parts of calcined kaolin, 11 parts of precipitated barium sulfate, 4 parts of active magnesium oxide, 1.4 parts of antioxidant 445, 0.6 parts of antioxidant RD, 0.5 parts of ultraviolet absorber UV-531, 0.55 parts of hindered amine light stabilizer 944, 1.5 parts of microcrystalline wax, 7 parts of trioctyl trimellitate, 0.75 parts of stearic acid, 1.3 parts of dicumyl peroxide, and 0.75 parts of triallyl isocyanurate.
[0080] B1: Add chlorinated polyethylene rubber and EPDM rubber to a mixer and mix at 77.5℃ and 37.5rpm for 3 minutes. Then add hydrogenated nitrile butadiene rubber and continue mixing for 3 minutes. Add activated magnesium oxide and stearic acid and mix for 2.5 minutes. Add carbon black N550, calcined kaolin, precipitated barium sulfate and trioctyl trimellitate. After all the additions are complete, continue mixing at 85℃ and 48rpm for 10 minutes.
[0081] B2: Add antioxidant 445, antioxidant RD, UV absorber UV-531, hindered amine light stabilizer 944 and microcrystalline wax, continue mixing at 77.5℃ for 4 minutes and then discharge the glue, controlling the discharge temperature to 100℃.
[0082] B3: Cool the rubber compound to below 50°C, add dicumyl peroxide and triallyl isocyanurate on an open mill with a roller temperature of 37.5°C, a front-to-back roller speed ratio of 1:1.2, and a roller gap of 0.9mm, and pass it through the mill 4 times; let the rubber compound that has passed through the mill stand at 25°C for 9 hours to obtain an anti-aging and anti-corrosion outer sheath material.
[0083] Example 3
[0084] A method for preparing an anti-aging and corrosion-resistant cable includes the following steps:
[0085] S1: Select nickel-plated soft copper monofilaments with a diameter of 0.3mm and a nickel layer thickness of 4μm, stranded in layers according to a 1+6+12+18 structure. The pitch ratios of the innermost, middle, and outermost strands are 11, 10, and 9, respectively, and the conductor compaction coefficient is 0.91. The stranding speed is 35m / min, and the tension of each stranded monofilament is 6N. Wrap a 0.14mm thick phlogopite tape around the conductor at a speed of 30m / min, with a wrapping overlap rate of... 45%, wrapping tension is 8N; heat-resistant silicone rubber insulation material is extruded onto the outside of phlogopite mica tape through a rubber extruder. The temperatures of the feeding section, plasticizing section, homogenizing section and die head of the rubber extruder are 55℃, 65℃, 75℃ and 85℃ respectively, the screw speed is 35rpm, and the nominal thickness of the insulation layer is 1.8mm; continuous hot air vulcanization is carried out at 205℃ for 10min, followed by cooling with room temperature air until the surface temperature of the insulated wire core does not exceed 50℃, thus obtaining the insulated wire core;
[0086] S2: Using an FEP film with a thickness of 0.15mm and a width of 18mm, the first FEP film layer is wrapped in a first spiral direction with an overlap rate of 60%, a wrapping linear speed of 12m / min, and a wrapping tension of 8N. A ring-shaped hot air heater is used to raise the outer surface temperature of the first FEP film layer to 330℃, and the overlap is pressed together with a pressure of 0.24MPa. During this hot melt pressing process, the maximum temperature of the outer surface of the heat-resistant silicone rubber insulation layer is controlled not to exceed 180℃, and it is cooled to a surface temperature below 80℃. Then, the same specifications are used... The FEP film is wrapped around the second FEP film layer in a second spiral direction opposite to the first spiral direction, so that the overlap seam of the second FEP film layer is offset from the overlap seam of the first FEP film layer by 50% of the cable circumference in the circumferential direction; the outer surface temperature of the second FEP film layer reaches 330°C, and the overlap part is heat-melted and pressed together with a pressure of 0.24MPa. During this heat-melting and pressing process, the maximum temperature of the outer surface of the heat-resistant silicone rubber insulation layer is controlled not to exceed 180°C. After cooling, a continuous fluoropolymer barrier sleeve with a total thickness of 0.3mm is formed.
[0087] S3: The FEP monofilaments are divided into a first FEP monofilament group and a second FEP monofilament group, each group consisting of 6 FEP monofilaments evenly arranged along the circumference of the cable; the two groups of FEP monofilaments are wound around the second FEP film layer in left-hand and right-hand directions respectively, with a pitch of 18mm. The absolute values of the winding angles relative to the cable axis of the two groups are equal, forming a diamond grid. The crossing angle of the two groups of FEP monofilaments is 80°, the winding linear speed is 12m / min, and the monofilament tension is 6N; short, spaced-out fusion splice zones are set along the length of the FEP monofilaments, with the axis of adjacent fusion splice zones... The spacing is 12mm, and the axial length of a single weld zone is 5mm. A grooved limiting pressure roller is used to perform local welding under the conditions of 280℃, single-point heating time of 2.5s, and pressure roller pressure of 0.15MPa, so that the depth of the FEP monofilament fused into the surface of the second FEP film layer is 40% of the thickness of the second FEP film layer. The minimum remaining thickness of the continuous fluoropolymer barrier sleeve at the weld zone is not less than 80% of the total thickness. After welding, an 8kV high-voltage spark test is used to confirm that there are no penetration defects in the continuous fluoropolymer barrier sleeve, and a non-penetrating heat-set FEP anchor grid is obtained.
[0088] S4: The anti-aging and corrosion-resistant outer sheath material is extruded onto the outside of the non-penetrating heat-set FEP anchoring grid using a rubber extruder. The temperatures of the feeding section, plasticizing section, homogenizing section, and die head of the rubber extruder are 55℃, 65℃, 70℃, and 80℃, respectively, and the screw speed is 30 rpm. This forms an anti-aging and corrosion-resistant outer sheath with a nominal thickness of 2.8 mm. The minimum coverage thickness of the outer sheath on the outside of the top of the FEP monofilament is 1.2 mm. The material is then continuously vulcanized with hot air at 175℃ for 12 minutes.
[0089] S5: After vulcanization, the cable is heat-treated at 155°C for 3 hours, then slowly cooled in a circulating hot air environment at 100°C for 40 minutes, and then cooled in room temperature air until the surface temperature of the cable does not exceed 40°C, thus obtaining an anti-aging and anti-corrosion cable.
[0090] Preparation of heat-resistant silicone rubber insulation material: By weight, take 100 parts of methyl vinyl phenyl silicone rubber, 32 parts of precipitated silica, 18 parts of spherical alumina, 15 parts of calcined kaolin, 2.0 parts of iron oxide red, 5 parts of phenyl silicone oil and 1.2 parts of 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane;
[0091] A1: Add methyl vinyl phenyl silicone rubber and phenyl silicone oil to a mixer and mix at 65°C and 50 rpm for 5 min; add precipitated silica in two batches, mixing for 5 min after each addition; then add spherical alumina, calcined kaolin and iron oxide red, and continue mixing at 75°C and 60 rpm for 12 min, controlling the discharge temperature to 100°C to obtain insulating base rubber;
[0092] A2: Cool the insulating base rubber to below 50°C, add 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane, and pass it through a two-roll mill with a roller temperature of 45°C, a front-to-back roller speed ratio of 1:1.3, and a roller gap of 1.0 mm 5 times; let the rubber compound after passing through the two-roll mill stand at 30°C for 12 hours to obtain heat-resistant silicone rubber insulating material.
[0093] Preparation of FEP monofilament: FEP resin was dried at 130℃ for 5 hours and then fed into a single-screw extruder. The temperatures of the feeding section, compression section, metering section, and die head were 320℃, 340℃, 360℃, and 355℃, respectively, and the screw speed was 45 rpm. A circular die with a diameter of 1.15 mm was used, and the extrusion rate was adjusted to stabilize the melt. After air cooling, the melt was drawn and sized at a traction ratio of 2.5. Then, it was continuously annealed and shaped at 245℃ for 90 seconds and cooled to below 60℃ to obtain FEP monofilament with a diameter of 0.7 mm and a diameter deviation of no more than ±0.03 mm.
[0094] Preparation of anti-aging and anti-corrosion outer sheath material: By weight, take 60 parts of chlorinated polyethylene rubber, 30 parts of hydrogenated nitrile rubber, 25 parts of ethylene propylene diene monomer (EPDM) rubber, 26 parts of carbon black N550, 20 parts of calcined kaolin, 14 parts of precipitated barium sulfate, 5 parts of active magnesium oxide, 1.8 parts of antioxidant 445, 0.8 parts of antioxidant RD, 0.7 parts of ultraviolet absorber UV-531, 0.8 parts of hindered amine light stabilizer 944, 2.0 parts of microcrystalline wax, 9 parts of trioctyl trimellitate, 1.0 part of stearic acid, 1.6 parts of dicumyl peroxide, and 1.0 part of triallyl isocyanurate.
[0095] B1: Add chlorinated polyethylene rubber and EPDM rubber to a mixer and mix at 85°C and 45 rpm for 4 min. Then add hydrogenated nitrile butadiene rubber and continue mixing for 4 min. Add activated magnesium oxide and stearic acid and mix for 3 min. Add carbon black N550, calcined kaolin, precipitated barium sulfate and trioctyl trimellitate. After all the additions are complete, continue mixing at 95°C and 55 rpm for 12 min.
[0096] B2: Add antioxidant 445, antioxidant RD, UV absorber UV-531, hindered amine light stabilizer 944 and microcrystalline wax, continue mixing at 85℃ for 5 minutes and then discharge the glue, controlling the discharge temperature to 105℃.
[0097] B3: Cool the rubber compound to below 50°C, add dicumyl peroxide and triallyl isocyanurate to an open mill with a roller temperature of 45°C, a front-to-back roller speed ratio of 1:1.3, and a roller gap of 1.2mm, and pass it through the mill 5 times; let the rubber compound that has passed through the mill stand at 30°C for 12 hours to obtain an anti-aging and anti-corrosion outer sheath material.
[0098] Comparative Example 1
[0099] Compared with Example 1, this comparative example replaces "the second layer of FEP film is wrapped in the opposite direction and the seam is staggered by 20% of the cable circumference" with the same operation "the second layer of FEP film is wrapped in the same direction and the two layers overlap completely". The remaining steps and parameters are the same, and will not be repeated in this comparative example. Finally, an anti-aging and anti-corrosion cable is obtained.
[0100] Comparative Example 2
[0101] Compared with Example 1, this comparative example does not use FEP monofilament anchoring grid, but directly extrudes the outer sheath on the outer layer of the second FEP film; the remaining steps and parameters are the same, and will not be repeated in this comparative example, and finally an anti-aging and anti-corrosion cable is obtained.
[0102] Comparative Example 3
[0103] Compared with Example 1, this comparative example replaces "left-handed first FEP monofilament group + right-handed second FEP monofilament cross mesh" with the same operation "only one set of FEP monofilaments is wound in one direction, without cross anchoring mesh"; the rest of the steps and parameters are the same, and will not be repeated in this comparative example. Finally, an anti-aging and anti-corrosion cable is obtained.
[0104] Comparative Example 4
[0105] Compared with Example 1, this comparative example replaces "hydrogenated nitrile rubber" with an equal mass of "chlorinated polyethylene rubber"; the remaining steps and parameters are the same, and will not be repeated in this comparative example. Finally, an anti-aging and anti-corrosion cable is obtained.
[0106] Comparative Example 5
[0107] Compared with Example 1, this comparative example replaces "ethylene propylene diene monomer (EPDM) rubber" with an equal mass of "chlorinated polyethylene rubber"; the remaining steps and parameters are the same, and will not be repeated in this comparative example. Finally, an anti-aging and anti-corrosion cable is obtained.
[0108] Comparative Example 6
[0109] Compared with Example 1, this comparative example replaces "active magnesium oxide" with an equal mass of "stearic acid"; the remaining steps and parameters are the same, and will not be repeated in this comparative example. Finally, an anti-aging and anti-corrosion cable is obtained.
[0110] Comparative Example 7
[0111] Compared with Example 1, this comparative example replaces "stearic acid" with an equal mass of "active magnesium oxide"; the remaining steps and parameters are the same, and will not be repeated in this comparative example. Finally, an anti-aging and anti-corrosion cable is obtained.
[0112] Comparative Example 8
[0113] Compared with Example 1, this comparative example replaces "spherical alumina" with an equal mass of "methyl vinyl phenyl silicone rubber"; the remaining steps and parameters are the same, and will not be repeated in this comparative example. Finally, an anti-aging and anti-corrosion cable is obtained.
[0114] Comparative Example 9
[0115] Compared with Example 1, this comparative example replaces "iron oxide red" with an equal mass of "methyl vinyl phenyl silicone rubber"; the remaining steps and parameters are the same, and will not be repeated in this comparative example. Finally, an anti-aging and anti-corrosion cable is obtained.
[0116] Comparative Example 10
[0117] Compared with Example 1, this comparative example replaces "trioctyl trimellitate" with an equal mass of "methyl vinyl phenyl silicone rubber"; the remaining steps and parameters are the same, and will not be repeated in this comparative example. Finally, an anti-aging and anti-corrosion cable is obtained.
[0118] Comparative Example 11
[0119] Compared with Example 1, the "microcrystalline wax" in this comparative example is replaced with an equal mass of "methyl vinyl phenyl silicone rubber"; the remaining steps and parameters are the same, and will not be repeated in this comparative example. Finally, an anti-aging and anti-corrosion cable is obtained.
[0120] The anti-aging and corrosion-resistant cables prepared in Examples 1-3 and Comparative Examples 1-11 were subjected to performance testing. Unless otherwise specified, no fewer than 5 parallel samples were set for each test and the average value was taken. The test methods are as follows, and the results are recorded in Tables 1-4.
[0121] 1. Hot air aging: Prepare dumbbell-shaped outer sheath specimens according to GB / T 2951.11-2008 and determine the initial tensile strength. Aging them at 150℃ for 168h according to GB / T 2951.12-2008, determine the tensile strength after aging, and calculate the tensile strength retention rate.
[0122] 2. Fluorescent UV aging: In accordance with GB / T 16422.3-2022, a UVA-340 lamp was used for 1000h cyclic exposure, in which each cycle included 8h of UV irradiation at 60℃ and 4h of condensation at 50℃; after the test, the tensile strength retention rate of the outer sheath was measured and surface cracking was observed.
[0123] 3. Ozone resistance: Refer to GB / T 2951.21-2008, stretch the outer sheath sample by 20%, place it at 40℃ and ozone concentration of 50pphm for 72h, observe the cracks with a 10x magnifying glass, and record them as no cracks, slight cracks, and obvious cracks.
[0124] 4. Mass Change in Acid and Alkali Media: Following GB / T 1690-2010, prepare 50mm×25mm×2mm samples from the outer sheath. After conditioning at 23±2℃ and 50%±5% relative humidity for 24 hours, weigh the initial mass m0. Immerse the samples in 10% sulfuric acid solution and 10% sodium hydroxide solution respectively, maintaining at 80℃ for 168 hours. After removal, clean and dry according to the same procedure, and condition at 23±2℃ for 24 hours before weighing the final mass m1. The mass change rate is calculated according to... Calculate, where m0 is the mass of the sample before soaking, and m1 is the mass of the sample after soaking and adjustment.
[0125] 5. Salt spray corrosion protection: Referring to GB / T 2423.17-2024, the two ends of a 500mm long finished cable were sealed and placed in a 5% sodium chloride salt spray at 35℃ for 240 hours. After the test, the outer sheath, FEP anchoring grid, FEP film layer, heat-resistant silicone rubber insulation layer, and mica wrapping layer were stripped. Five single filaments were randomly selected from the outermost strand of the conductor and straightened. Four images of each single filament were taken at 90° intervals along the circumference under D65 standard light source, fixed exposure, and 10x magnification. The same color threshold was used for binarization segmentation. The corrosion area ratio of the outer conductor single filament surface was calculated based on the ratio of the number of corrosion spot pixels to the number of effective surface pixels. The average value of 20 images was taken. The insulation resistance retention rate was determined according to GB / T 3048.5-2007.
[0126] 6. Axial holding force and temperature cycling: Cut a cable sample with a length of 250mm. Remove 50mm of the outer sheath from one end and fix the insulated core. Clamp the outer sheath at the other end, with an effective clamping length of 100mm. Use a universal testing machine to apply a tensile load along the axial direction at a tensile rate of 50mm / min. Record the maximum force before the displacement of the outer sheath relative to the insulated core reaches 1.0mm as the initial axial holding force. In addition, subject the sample to a temperature cycle of -40℃ to 150℃ 100 times, holding each temperature end for 30min. Repeat the test after each cycle and calculate the holding rate.
[0127] 7. Bending durability and spark test: With a bending radius of 6 times the outer diameter of the finished cable, perform ±90° reciprocating bending 10,000 times at a frequency of 30 times / min; after bending, check the outer sheath movement, FEP film whitening and grid desoldering, and perform extrusion sheath spark test according to GB / T 3048.10-2007, and record whether a breakdown alarm occurs.
[0128] 8. Thermal conductivity and high-temperature electrical stability of the insulation layer: 100mm×100mm×2mm plate-shaped samples were prepared from the heat-resistant silicone rubber insulation layer, and the thermal conductivity was determined by steady-state heat flow method at 25℃. Another insulation sample was aged in hot air at 200℃ for 168h, cooled, and conditioned at 23℃ for 24h. The volume resistivity at 20℃ was determined according to the basic principle of GB / T 3048.5-2007. The breakdown strength before and after aging was determined by using a 50Hz power frequency voltage with a step-up rate of 500V / s, and the breakdown strength retention rate was calculated.
[0129] Table 1. Results of Aging and Acid / Alkali Media Stability Tests for Outer Sheath
[0130]
[0131] Table 2. Test results of corrosive media barrier and salt spray protection
[0132]
[0133] Table 3 Results of interlayer anchorage and bending durability tests
[0134]
[0135] Table 4. Test results of thermal conductivity and high-temperature electrical stability of insulation layer
[0136]
[0137] According to the exemplary target data in Tables 1-4, the embodiments 1-3 of the present invention have a good overall balance in terms of outer sheath thermo-oxidative aging, ultraviolet aging, ozone resistance, acid and alkali media stability, FEP continuous barrier, salt spray protection, interlayer anchoring, bending durability, and insulation thermal conductivity and high-temperature electrical stability.
[0138] A comparison of Example 1 and Comparative Example 1 shows that Comparative Example 1 changed the second FEP film layer to wrap around the first FEP film layer in the same direction, and made the overlap joint of the two layers completely overlap. This change has little effect on the thermo-oxidative, ultraviolet, ozone, and acid-alkali immersion properties of the outer sheath material itself, but the conductor corrosion area ratio and the number of spark alarms increased significantly after salt spray, the axial retention rate decreased after temperature cycling, and whitening and local opening appeared at the overlap joint after bending. This indicates that reverse wrapping and circumferential misalignment of the joint can make the overlap paths of the two layers mutually shield each other, prolong the migration path of the corrosive medium, and reduce the possibility of stress concentration at the same joint position caused by temperature cycling and repeated bending.
[0139] A comparison of Example 1 and Comparative Example 2 shows that, omitting the FEP monofilament anchoring grid results in a lack of geometric interlocking between the outer sheath and the low surface energy FEP film. The initial axial holding force decreases from 360N to 65N, and the retention rate drops to 32% after temperature cycling. Significant axial movement also occurs after bending. This indicates that the non-penetrating FEP monofilament anchoring grid primarily serves as the mechanical lock and stress transfer mechanism between the outer sheath and the continuous fluoropolymer barrier sleeve.
[0140] A comparison of Example 1 and Comparative Example 3 shows that, while a certain degree of mechanical anchoring still exists when only unidirectional FEP monofilaments are used, a left-right helical cross-grid cannot be formed, making it difficult for the outer sheath material to simultaneously form a uniform, continuous adhesive connection in both the circumferential and axial directions. Therefore, the initial axial holding force and retention rate after temperature cycling in Comparative Example 3 are significantly lower than those in Example 1, and localized torsion, axial movement, and whitening of the unidirectional stress area occur after bending. This indicates that the left-right helical FEP monofilament cross-grid arrangement can disperse axial loads and suppress the accumulation of unidirectional shrinkage.
[0141] A comparison of Example 1 and Comparative Example 4 shows that replacing an equal amount of hydrogenated nitrile rubber with chlorinated polyethylene rubber reduces the retention rate of the outer sheath during 150°C hot air aging, increases the rate of mass change after acid and alkali immersion, and enhances the degree of performance degradation after salt spraying. Furthermore, surface microcracks appear after bending. This indicates that hydrogenated nitrile rubber is beneficial for improving the heat and oxygen stability, mechanical strength, and media resistance of the co-crosslinked outer sheath, and can reduce the risk of surface microcracks after long-term aging.
[0142] A comparison of Example 1 and Comparative Example 5 shows that after replacing EPDM rubber with an equal amount of chlorinated polyethylene rubber, the acid-base mass change rate of the outer sheath did not increase significantly, but the ozone resistance, fracture deformation capacity, and flexural life decreased significantly, with cracks appearing after approximately 3500 bends. This indicates that EPDM rubber mainly provides ozone resistance, elastic recovery, and flexibility in the co-crosslinking system, serving to buffer the shrinkage and deformation differences between the FEP barrier sleeve and the outer sheath during temperature cycling and repeated bending.
[0143] A comparison of Example 1 and Comparative Example 6 shows that after replacing an equal amount of active magnesium oxide with stearic acid, the system lacks effective capture of acidic small molecules during the aging process of chlorinated rubber. The retention rate of the outer sheath during hot air aging, acid-base stability, insulation resistance retention rate after salt spray, and axial retention rate after temperature cycling all significantly decrease. This indicates that active magnesium oxide can act as an acid product capture agent, slowing down the autocatalytic dechlorination and crosslinking network embrittlement of chlorinated polyethylene rubber.
[0144] A comparison of Example 1 and Comparative Example 7 shows that while replacing stearic acid with an equal amount of activated magnesium oxide retained the ability to capture acidic products, the rubber compound lacked necessary lubrication and processing conditioning components, leading to a decrease in filler dispersion and extrusion surface quality. Comparative Example 7 exhibited a rough outer sheath surface with microcracks, and a decrease in acid-base mass change rate, salt spray protection, and temperature cycling retention rate. This indicates that stearic acid and activated magnesium oxide have different functions; the former mainly improves mixing dispersion and processing stability, while the latter primarily undertakes the role of capturing acidic products. The two cannot be simply substituted for each other.
[0145] A comparison of Example 1 and Comparative Example 8 shows that after replacing an equal amount of spherical alumina with methyl vinyl phenyl silicone rubber, the aging and anchoring performance of the outer sheath remained essentially unchanged. However, the thermal conductivity of the insulation layer at 25°C decreased from 0.47 W / (m·K) to 0.25 W / (m·K), and the volume resistivity and breakdown strength retention rate after aging at 200°C were significantly reduced. This indicates that spherical alumina can construct heat conduction paths within the insulation layer, reducing local heat accumulation and thus contributing to maintaining the electrical insulation stability after high-temperature aging.
[0146] A comparison of Example 1 and Comparative Example 9 shows that after replacing an equal amount of iron oxide red with methyl vinyl phenyl silicone rubber, the thermal aging performance remained largely unchanged, but the volume resistivity and breakdown strength retention rate after aging at 200°C decreased significantly. This indicates that iron oxide red mainly plays a role in heat resistance stabilization and hot air aging inhibition in this insulation system, and its function differs from the thermal conductivity of spherical alumina. The synergy of both helps to improve the long-term high-temperature electrical stability of the heat-resistant silicone rubber insulation layer.
[0147] A comparison of Example 1 and Comparative Example 10 shows that replacing trioctyl trimellitate with an equal mass of methyl vinylphenyl silicone rubber results in the silicone rubber not performing the same plasticizing, wetting, and viscosity-reducing effects as trioctyl trimellitate in the blend system of chlorinated polyethylene rubber, hydrogenated nitrile rubber, and EPDM rubber. This leads to insufficient filler wetting, decreased flowability of the outer sheath compound, and inadequate filling of the FEP anchoring grid voids. Consequently, Comparative Example 10 exhibits decreased retention rates under hot air and UV aging, increased acid-base mass change rate and conductor corrosion area after salt spray, decreased initial axial holding force, reduced axial holding rate after temperature cycling, and earlier cracking during repeated bending. This indicates that trioctyl trimellitate is beneficial for improving the processing flowability of the outer sheath, filler dispersion, low-temperature flexibility, and grid coverage integrity.
[0148] A comparison of Example 1 and Comparative Example 11 shows that after replacing the microcrystalline wax with an equal mass of methyl vinyl phenyl silicone rubber, the outer sheath surface cannot continuously form a migration protective film with a certain degree of density and renewability. Ultraviolet radiation, ozone, water vapor, and corrosive media can more easily act directly on the rubber surface. Comparative Example 11 showed a significant decrease in the retention rate of its UV-aged tensile strength, obvious cracks after the ozone test, and increased acid-base mass change rate and conductor corrosion area after salt spray. Surface cracking also occurred after bending. This indicates that the microcrystalline wax, by slowly migrating to the outer sheath surface to form a physical shielding layer, can work together with UV absorbers, hindered amine light stabilizers, and antioxidants to improve the weather resistance, ozone resistance, and surface corrosion resistance of the outer sheath.
[0149] Based on the test results of the comprehensive embodiments and comparative examples, it can be seen that the present invention, through the synergistic effect of technical measures such as reverse staggered hot-melt barrier of double-layer FEP film, non-penetrating cross-anchoring of left and right spiral FEP monofilaments, co-crosslinking of chlorinated polyethylene rubber / hydrogenated nitrile rubber / EPDM rubber, active magnesium oxide acid capture, trioctyl trimellitate plasticizing wetting, microcrystalline wax migration protection, and spherical alumina thermal conductivity and iron oxide red heat resistance stabilization, controls failure paths such as the migration of corrosive media along the joints, axial movement of the outer sheath, thermo-oxidative and ozone aging, ultraviolet cracking, acidic degradation of chlorinated rubber, rubber processing defects, and thermal accumulation of the insulation layer, thereby achieving a comprehensive improvement in anti-aging, corrosion resistance, bending resistance, and high-temperature electrical stability.
[0150] The above description is merely an example and illustration of the concept of the present invention. Those skilled in the art can make various modifications or additions to the specific embodiments described or use similar methods to replace them, as long as they do not deviate from the concept of the invention or exceed the scope defined in the claims, they should all fall within the protection scope of the present invention.
Claims
1. An anti-aging and corrosion-resistant cable, characterized in that, From the inside to the outside along the radial direction, it includes a conductor, a fire-resistant mica wrapping layer, a heat-resistant silicone rubber insulation layer, a first FEP film layer, a second FEP film layer, a non-penetrating heat-set FEP anchoring grid, and an anti-aging and anti-corrosion outer sheath. The first FEP film layer is wrapped around the heat-resistant silicone rubber insulation layer along the first spiral direction, and the second FEP film layer is wrapped around the first FEP film layer along the second spiral direction opposite to the first spiral direction. The overlap joints of the first FEP film layer and the second FEP film layer are staggered along the circumference of the cable, and their respective overlap parts are surface heat-fused and pressed together, so that the first FEP film layer and the second FEP film layer together form a continuous fluoropolymer barrier sleeve without through holes. The non-penetrating heat-set FEP anchoring grid includes a first FEP monofilament group wound in a left-handed direction and a second FEP monofilament group wound in a right-handed direction. The first and second FEP monofilament groups are partially fused with the surface of the second FEP film layer in the contact area, and do not penetrate the continuous fluoropolymer barrier sleeve. The anti-aging and anti-corrosion outer sheath covers the first and second FEP monofilament groups and forms a continuous colloidal bridge between adjacent FEP monofilaments to constitute a non-penetrating geometric anchoring of the outer sheath.
2. The anti-aging and corrosion-resistant cable according to claim 1, characterized in that, The thickness of the first FEP film layer and the second FEP film layer are 0.05-0.15 mm, the film width is 10-18 mm, and the wrapping overlap rate is 45%-60%. The circumferential offset of the joint between the first FEP film layer and the second FEP film layer is 20%-50% of the cable circumference. The total thickness of the continuous fluoropolymer barrier sleeve formed after hot-melt pressing is 0.12-0.30 mm.
3. The anti-aging and corrosion-resistant cable according to claim 1, characterized in that, The FEP monofilaments used in the first and second FEP monofilament groups have a diameter of 0.30-0.70 mm and a pitch of 6-18 mm, respectively. The cross angle between the two FEP monofilament groups is 40°-80°. The depth to which the FEP monofilaments are melted into the surface of the second FEP film layer is 15%-40% of the thickness of the second FEP film layer. The minimum remaining thickness of the continuous fluoropolymer barrier sleeve at the weld area is not less than 75% of the total thickness.
4. The anti-aging and corrosion-resistant cable according to claim 1, characterized in that, The anti-aging and anti-corrosion outer sheath comprises, by weight parts: 50-60 parts chlorinated polyethylene rubber, 20-30 parts hydrogenated nitrile rubber, 15-25 parts ethylene propylene diene monomer (EPDM) rubber, 18-26 parts carbon black N550, 12-20 parts calcined kaolin, 8-14 parts precipitated barium sulfate, 3-5 parts active magnesium oxide, 1.0-1.8 parts antioxidant 445, 0.4-0.8 parts antioxidant RD, 0.3-0.7 parts ultraviolet absorber UV-531, 0.3-0.8 parts hindered amine light stabilizer 944, 1.0-2.0 parts microcrystalline wax, 5-9 parts trioctyl trimellitate, 0.5-1.0 parts stearic acid, 1.0-1.6 parts dicumyl peroxide, and 0.5-1.0 parts triallyl isocyanurate.
5. The anti-aging and corrosion-resistant cable according to claim 1, characterized in that, The heat-resistant silicone rubber insulation layer comprises, by weight, 100 parts of methyl vinyl phenyl silicone rubber, 24-32 parts of precipitated silica, 10-18 parts of spherical alumina, 8-15 parts of calcined kaolin, 1.0-2.0 parts of iron oxide red, 2-5 parts of phenyl silicone oil, and 0.8-1.2 parts of 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane.
6. The anti-aging and corrosion-resistant cable according to claim 1, characterized in that, The conductor is formed by layering nickel-plated soft copper monofilaments in a 1+6+12+18 structure. The diameter of the nickel-plated soft copper monofilaments is 0.18-0.30 mm, the thickness of the nickel layer is 1-4 μm, and the conductor compaction coefficient is 0.87-0.
91. The fire-resistant mica wrapping layer uses phlogopite tape with a thickness of 0.06-0.14 mm and a wrapping overlap rate of 20%-45%. The nominal thickness of the heat-resistant silicone rubber insulation layer is 1.0-1.8 mm.
7. A method for preparing the anti-aging and corrosion-resistant cable according to any one of claims 1-6, characterized in that, Includes the following steps: S1: Nickel-plated soft copper monofilaments are stranded in layers to form a conductor, gilt mica tape is wrapped around the conductor, and heat-resistant silicone rubber insulation is extruded. After hot air vulcanization and cooling, the insulated wire core is obtained. S2: Wrap a first FEP film layer around the outside of the insulated wire core along the first spiral direction, and perform short-term surface heating, pressing and cooling on the overlapping part of the first FEP film layer; then wrap a second FEP film layer along the second spiral direction opposite to the first spiral direction, so that the overlapping seam of the first FEP film layer and the second FEP film layer is staggered in the circumferential direction, and perform short-term surface heating and pressing on the overlapping part of the second FEP film layer to form a continuous fluoropolymer barrier sleeve; S3: FEP resin is extruded, drawn and sized, and annealed to form FEP monofilaments. Two sets of FEP monofilaments are wound around the second FEP film layer in the left-hand and right-hand directions, respectively, and the FEP monofilaments are partially fused with the surface of the second FEP film layer to form a non-penetrating heat-set FEP anchoring grid. S4: Prepare anti-aging and anti-corrosion outer sheath material, and extrude the outer sheath material into the outside of the non-penetrating heat-set FEP anchoring grid, and form an anti-aging and anti-corrosion outer sheath by continuous hot air vulcanization; S5: After vulcanization, the cable undergoes post-heat treatment and graded cooling to obtain an anti-aging and corrosion-resistant cable.
8. The preparation method according to claim 7, characterized in that, After the first FEP film layer in S2 is wrapped, a ring-shaped hot air heater is used to heat and press the overlapping area. After cooling, the second FEP film layer is wrapped, and the overlapping area of the second FEP film layer is heated and pressed in the same way. During the two hot-melt pressing processes, the outer surface temperature of the corresponding FEP film layer is 300-330℃, and the pressing pressure is 0.08-0.24MPa. During the two hot-melt pressing processes, the maximum temperature of the outer surface of the heat-resistant silicone rubber insulation layer does not exceed 180℃. In S3, the FEP resin has a temperature of 110-13... The material is dried at 0℃ for 3-5 hours, then melt-extruded using a single-screw extruder. The temperature of the feeding section of the single-screw extruder is 300-320℃, the temperature of the compression section is 320-340℃, the temperature of the metering section is 335-360℃, and the temperature of the die head is 330-355℃. After air cooling and 1.2-2.5 times traction sizing, the melt is continuously annealed and shaped at 220-245℃ for 30-90 seconds to obtain FEP monofilaments. The local fusion temperature of the FEP monofilaments and the second FEP film layer is 260-280℃, and the single-point heating time is 0.5-2.5 seconds.
9. The preparation method according to claim 7, characterized in that, The preparation method of the heat-resistant silicone rubber insulation material is as follows: A1: Add methyl vinyl phenyl silicone rubber and phenyl silicone oil to a mixer and mix at 50-65℃ and 30-50rpm for 3-5 minutes; add precipitated silica in two batches, mixing for 3-5 minutes after each addition; then add spherical alumina, calcined kaolin and iron oxide red, and continue mixing at 55-75℃ and 40-60rpm for 8-12 minutes, controlling the discharge temperature at 90-100℃ to obtain the insulating base adhesive; A2: Cool the insulating base rubber to below 50℃, add 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane, and pass it through a two-roll mill with a roll temperature of 30-45℃ and a roll gap of 0.5-1.0mm 3-5 times. Let it stand for 4-12 hours to obtain heat-resistant silicone rubber insulation material.
10. The preparation method according to claim 7, characterized in that, The preparation method of the anti-aging and anti-corrosion outer sheath material is as follows: B1: Add chlorinated polyethylene rubber and EPDM rubber to a mixer and mix at 70-85℃ and 30-45rpm for 2-4 minutes. Then add hydrogenated nitrile butadiene rubber and continue mixing for 2-4 minutes. Add activated magnesium oxide and stearic acid and mix for 2-3 minutes. Add carbon black N550, calcined kaolin, precipitated barium sulfate, and trioctyl trimellitate. After all the additions are complete, continue mixing at 75-95℃ and 40-55rpm for 8-12 minutes. B2: Add antioxidant 445, antioxidant RD, UV absorber UV-531, hindered amine light stabilizer 944 and microcrystalline wax, continue mixing at 70-85℃ for 3-5 minutes and then discharge the glue, controlling the discharge temperature to 95-105℃. B3: Cool the rubber compound to below 50°C, add dicumyl peroxide and triallyl isocyanurate to a two-roll mill, pass through 3-5 times and let stand for 6-12 hours to obtain an anti-aging and corrosion-resistant outer sheath material. The extrusion temperature of the outer sheath material is 45-80°C, the continuous hot air vulcanization temperature is 165-175°C and the vulcanization time is 8-12 minutes, and the post-heat treatment temperature in S5 is 140-155°C and the time is 1-3 hours.